The carbohydrate metabolism and expression of carbohydrate-active enzyme genes in Aspergillus luchuensis fermentation of tea leaves - Li, Ruoyu; Wang, Teng; Bo, Nianguo; Wang, Qi; Chen, Qiuyue; Liang, Zhengwei; Guan, Yanhui; Jiang, Bin; Ma, Yan; Zhao, Ming (Frontiers in Microbiology, 2024)
Carbohydrates that make up 20% to 25% of tea beverages are responsible for their flavor and bioactivity. Pu-erh tea's carbohydrates change during microbial fermentation and require further research. In this study, we examined the carbohydrate metabolism and expression of carbohydrate-active enzyme genes during the fermentation of tea leaves with Aspergillus luchuensis. Widely targeted metabolomics analysis, high performance anion exchange chromatography measurements and transcriptomics were used in this study. After fermentation, the levels of soluble sugar, hemicellulose, lignin, eight monosaccharides, and seven sugar alcohols increased. Meanwhile, the relative contents of polysaccharides, D-sorbitol, D-glucose, and cellulose decreased. High expression of 40 genes encoding 16 carbohydrate enzymes was observed during fermentation (FPKM>10). These genes encode L-iditol 2-dehydrogenase, pectinesterase, polygalacturonase, α-amylase, glucoamylase, endoglucanase, β-glucosidase, β-galactosidase, α-galactosidase, α-glucosidase, and glucose-6-phosphate isomerase, among others. These enzymes are known to break down polysaccharides and cell wall cellulose, increasing the content of monosaccharides and soluble sugar.